Women use credit for computers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Using micro-credit loans to finance computers and email subscriptions for rural women has earned the Fantsuam Foundation's Bayanloco Community Learning Centre in Kaduna State, Nigeria, the first APC Africa Hafkin Communications Prize. The prize was...